Species diversity and composition, conservation status, and carbon stocks of the mangrove forests in Zamboanga City, Philippines - PATRICIA ANGELA S. EPAN; ARMI G. TORRES; JENNET R. MAG-ASO; WELLA A. TIU-TATIL (Society for Indonesian Biodiversity, 2026)
Abstract. Epan PAS, Torres AG, Mag-Aso JR, Tiu-Tatil WA. 2026. Species diversity and composition, conservation status, and carbon stocks of the mangrove forests in Zamboanga City, Philippines. Biodiversitas 27 (6): d270608. https://doi.org/10.13057/biodiv/d270608. Mangrove ecosystems are essential protective barriers for coastal areas and provide important ecological services to society, such as shelter from storms and strong waves, habitat for a variety of fish species, and an extensive amount of carbon sequestration. However, specific data on the species composition and management strategies for this ecosystem are currently insufficient in Zamboanga City, Philippines. To address this gap, this study assessed the taxonomic diversity and composition, aboveground living biomass and carbon stock, and conservation status of mangrove forests in three sites: Talabaan, Victoria, and Great Sta. Cruz Island (GSCI). The field sampling was conducted in June, July, December of 2025, and January of 2026. In each study site, three 150-m transects were established perpendicular to the shoreline. Within each transect, eight 10 m x 10 m quadrats were systematically positioned at 10-m intervals, resulting in a cumulative sample size of n = 72 quadrats across the study area. A total of 15 mangrove species from 7 families and 8 genera were identified across all sites, with Rhizophora genus dominating (Rhizophora apiculata, 346 individuals; Rhizophora mucronata, 223 individuals). Taxonomic surveys revealed that while the majority of the identified species are categorized as 'Least Concern' by the IUCN, the presence of Avicennia marina var. rumphiana (Vulnerable) and Sonneratia ovata (Near Threatened) indicates the conservation importance of the study sites. Victoria exhibited a relatively high diversity (H' = 1.86), while Talabaan showed the lowest (H' = 1.39). GSCI recorded the highest carbon stock at 41.61 t C ha⁻¹ with a carbon equivalent of 152.71 t CO2 ha⁻¹. Results show that while reforested sites like Talabaan and Victoria contribute to mangrove vegetation cover, protected natural stands like GSCI remain superior in both carbon sequestration and biodiversity. By quantifying the ecological disparities between reforested and natural stands, this study provides localized ecological data that may serve as a preliminary baseline for future conservation planning and carbon sequestration strategies in Zamboanga Peninsula.